Pengaruh kompensasi financial dan kepemimpinan terhadap kepuasan kerja karyawan lokasi PT. Mandiri Jayaindo Utama Pekanbaru - Andy Leo; Dewita Suryati Ningsih; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Mandiri Jayaindo Utama Pekanbaru. This study aims to determine how Financial Compensation and Leadership either simultaneously or partially effect the Work Satisfaction Of Employee In PT. Mandiri Jayaindo Utama Pekanbaru.The population in this study is administrators and operators, amounting to 42 people, with a total sample of 42 employees. The method of analysis used in this study is the method regression analysis using SPSS version 16.00.Simultaneous regression test (F test) showed that the independent variables studied (Financial Compensation and Leadership) jointly (simultaneously) have a significant effect on the dependent variable (Work Satisfaction of Employee). The magnitude of the effect that (R2) by the two independent variables together against the dependent variable 51.10%, while the remaining 48.9% is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Financial Compensation and Leadership) has a significant effect on the dependent variable (Work Satisfaction of Employee).The company is suggested to rearrange its financial compensation aspect by accustoming its salary and bonus, then provide a good, diligent field-supervisor that cares about the employees so the employees can feel like working on the company.Keywords: Financial Compensation, Leadership, Work Satisfaction